ANALISIS ELECTRIC GROUNDING SYSTEM UNTUK KEANDALAN DAN KESELAMATAN DALAM INSTALASI KELISTRIKAN - Pujiyanto, Fajar; Susanto, Susanto (Majalah Ilmiah Gema Maritim, 2022)
Electrical installations need to be installed correctly by referring to the basic guidelines, namely the General Guidelines for Electrical Installation (PUIL) for the country of Indonesia, or referring to other guidelines with international standards, namely the International Electrotechnical Commission (IEC) and IEEE. Electrical installations must have a protection system, high reliability when operating, and the ability to respond to installation disturbances quickly. The protection system provides safety for living things, property, and the electrical installation itself. The grounding system is one of the protections to maintain the reliability of the installation and protect the safety of personnel, the grounding system serves to ensure a stable and safe power supply voltage. This study discusses the grounding system, namely grounding resistance (GR), and its relation to the grounding rod material and soil resistivity (SR). The writing of the paper used a qualitative descriptive method, the basic supporting material was carried out with a literature review and references to previous research. The assessment of the two components aims to produce a good grounding system with economical design and maintenance costs, it is stated that the grounding rod material and soil resistivity are important factors for the grounding installation system.